2010
DOI: 10.2119/molmed.2010.00195
|View full text |Cite
|
Sign up to set email alerts
|

Aging Influences Cardiac Mitochondrial Gene Expression and Cardiovascular Function following Hemorrhage Injury

Abstract: Cardiac dysfunction and mortality associated with trauma and sepsis increase with age. Mitochondria play a critical role in the energy demand of cardiac muscles, and thereby on the function of the heart. Specific molecular pathways responsible for mitochondrial functional alterations after injury in relation to aging are largely unknown. To further investigate this, 6-and 22-monthold rats were subjected to trauma-hemorrhage (T-H) or sham operation and euthanized following resuscitation. Left ventricular tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 61 publications
1
26
0
Order By: Relevance
“…In order to study nuclear-mitochondria cross talk, our laboratory developed a mitochondrial gene chip with probe sets representing the transcriptome of the genes on the mitochondria and that of the nucleus important for the structure and function of mitochondria, together called the mitoscriptome (Raju et al , 2011). We found significant upregulation of genes involved in glycolytic pathways in cardiomyocytes subjected to hypoxia demonstrating a shift in energy production from mitochondria to glycolysis (Jian et al , 2011b). Recently it has been found that humanin, a mitochondria derived peptide, exhibits strong cytoprotective actions against various stress and disease models and suggested to be part of a retrograde signaling that involves nuclear-mitochondria crosstalk (Gong et al , 2014).…”
Section: Hypoxic-ischemic Injurymentioning
confidence: 99%
See 3 more Smart Citations
“…In order to study nuclear-mitochondria cross talk, our laboratory developed a mitochondrial gene chip with probe sets representing the transcriptome of the genes on the mitochondria and that of the nucleus important for the structure and function of mitochondria, together called the mitoscriptome (Raju et al , 2011). We found significant upregulation of genes involved in glycolytic pathways in cardiomyocytes subjected to hypoxia demonstrating a shift in energy production from mitochondria to glycolysis (Jian et al , 2011b). Recently it has been found that humanin, a mitochondria derived peptide, exhibits strong cytoprotective actions against various stress and disease models and suggested to be part of a retrograde signaling that involves nuclear-mitochondria crosstalk (Gong et al , 2014).…”
Section: Hypoxic-ischemic Injurymentioning
confidence: 99%
“…c-MYC appears to act via increasing transcription factor A mitochondrial (TFAM) and is critically important in hypoxia/ischemia. In a mitochondrial gene expression profiling of a rat model of hemorrhagic shock in our laboratory, c-MYC exhibited most change following the injury (Jian et al , 2011b). …”
Section: Hypoxic-ischemic Injurymentioning
confidence: 99%
See 2 more Smart Citations
“…However the mechanisms by which aging adversely affect injury outcome are not fully elucidated. In the injury model, trauma-hemorrhage (T-H), we have recently demonstrated increased endoplasmic reticulum stress, decreased left ventricular performance and decreased mitochondrial function [810]. Hemorrhagic shock causes a whole body hypoxia/reoxygenation injury, leading to dysregulation of biochemical pathways and multiple organ dysfunction syndrome [1117].…”
Section: Introductionmentioning
confidence: 99%